La familia, primer ámbito de educación cívica* (2019)
The current historical and social circumstances, which evidence a deterioration of democracy and of the capacity to act as critical and reflexive citizens, demand the strengthening of both citizen training exercises and the role of new actors. In the present essay, the role of the family in civic education is explored. The text aims to demonstrate that the family is a central educational sphere in the formation of a set of civic virtues and, therefore, in the development of an ethical capacity for political action.